The organizing role of Wnt signaling pathway during arthropod posterior growth - Mundaca-Escobar, Marco; Cepeda, Rodrigo E.; Sarrazin, Andres F. (Frontiers in Cell and Developmental Biology, 2022)
Wnt signaling pathways are recognized for having major roles in tissue patterning and cell proliferation. In the last years, remarkable progress has been made in elucidating the molecular and cellular mechanisms that underlie sequential segmentation and axial elongation in various arthropods, and the canonical Wnt pathway has emerged as an essential factor in these processes. Here we review, with a comparative perspective, the current evidence concerning the participation of this pathway during posterior growth, its degree of conservation among the different subphyla within Arthropoda and its relationship with the rest of the gene regulatory network involved. Furthermore, we discuss how this signaling pathway could regulate segmentation to establish this repetitive pattern and, at the same time, probably modulate different cellular processes precisely coupled to axial elongation. Based on the information collected, we suggest that this pathway plays an organizing role in the formation of the body segments through the regulation of the dynamic expression of segmentation genes, via controlling the caudal gene, at the posterior region of the embryo/larva, that is necessary for the correct sequential formation of body segments in most arthropods and possibly in their common segmented ancestor. On the other hand, there is insufficient evidence to link this pathway to axial elongation by controlling its main cellular processes, such as convergent extension and cell proliferation. However, conclusions are premature until more studies incorporating diverse arthropods are carried out.